1966
DOI: 10.1002/cjce.5450440609
|View full text |Cite
|
Sign up to set email alerts
|

Solubility parameters of hydrocarbons

Abstract: Information available in the literature on vapor pressures, saturated vapor and liquid densities, and critical constants, for different hydrocarbons, has permitted the calculation of δ, the solubility parameter advanced by Hildebrand, at temperatures up to and including the critical point. For these hydrocarbons, the residual quantity, δ‐δc was found to depend on 1‐TR according to the relationship, where k appears to be a constant within different classes of hydrocarbons. Values of δ calculated with this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The solubility parameters are calculated from the following correlations (Bradford and Thodos, 1966;Hutchinson and Ray, 1990 …”
Section: Sorptionmentioning
confidence: 99%
“…The solubility parameters are calculated from the following correlations (Bradford and Thodos, 1966;Hutchinson and Ray, 1990 …”
Section: Sorptionmentioning
confidence: 99%
“…The solubility parameter of propane can be estimated using the Bradford and Thodos equations: δ 1 δ C = 15.24 ( 1 T r ) 0.446 where δ 1 is the solubility parameter of liquid propane, δ C is the solubility parameter of propane (4.83 MPa 1/2 ) at critical conditions, and T r is the reduced temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Yosim and Owens [21] used the density and Δ V data from a secondary source, from which the value H ( b ) MPa 1/2 = 14.56 is derived. Bradford and Thodos [66] reported expressions and parameters from which the solubility parameter was supposed to be calculated, but the resulting value (7.9 MPa 1/2 ) is too small. Gilmour et al [98] reported density and Δ V data from an undisclosed source, from which the value H ( b ) MPa 1/2 = 15.5 is deduced.…”
Section: 140mentioning
confidence: 99%
“…The latter authors provided Δ V ( b )/kcal mol −1 = 4.49, that is, 18686 J mol −1 at the boiling point b = 231.88 K, so that the same value H ( b ) = 14.90 MPa 1/2 is derived. Bradford and Thodos [66] reported the parameters of the following expression:…”
Section: Ethane Prausnitz and Shairmentioning
confidence: 99%
See 1 more Smart Citation